Digital health technologies for accessing contraceptive services among young people in Sub-Saharan Africa: A scoping review protocol. - Agnes Kyamulabi; Eva Oberle; Lotenna Olisaeloka; Innocent Kamya; Ingrid Nyesigire; Wendy V Norman; Abdul-Fatawu Abdulai (PLOS Digital Health, 2025)
This scoping review aims to examine and synthesize existing literature on the use of digital health technologies, with a focus on the extent and types of technologies used to access contraceptive services among young people in Sub-Saharan Africa (SSA). Globally, digital health technologies have emerged as pivotal tools in addressing contraceptive needs among young people. In SSA, where traditional healthcare systems often face numerous challenges, these technologies offer innovative solutions to improve access to contraceptive services. Despite growing interest in digital health technologies, comprehensive reviews on contraceptive access among young people in SSA are still lacking. Most existing studies focus broadly on sexual and reproductive health (SRH) or adult populations, leaving a gap in understanding the unique needs and experiences of young people using digital technologies for contraception services. It is unclear how much research has been conducted to examine how these technologies can facilitate contraceptive use, which technologies are used and why, where this evidence is concentrated within SSA, and the prevailing gaps. Therefore, we propose to undertake a scoping review. This scoping review will include studies focusing on young people aged 10-24 years in SSA, addressing access challenges to contraceptive services within this age group. The review will consider client-facing digital health technologies. All methodological approaches and designs will be included. Reviews, protocols, conference papers, policy briefs and studies conducted outside SSA will be excluded. The review will apply the comprehensive search strategy recommended by Joanna Briggs Institute (JBI). The initial limited search of MEDLINE (Ovid) and CINAHL Complete (EBSCOhost) was conducted with guidance from the University Librarian. This informed the selection of keywords, along with index terms, to develop a full search strategy for MEDLINE (Ovid), CINAHL Complete (EBSCOhost), Scopus, Compendix Engineering Village, and IEEE Xplore. The scoping review shall also use supplementary resources such as google scholar, and African Journal online (AJOL). We will also review the reference lists of articles that meet the inclusion criteria to ascertain articles that were not returned by the search criteria. Data will be presented using tables and charts, accompanied by a narrative summary. This scoping review was registered in Open Science Framework: https://doi.org/10.17605/OSF.IO/5QJ6P.